Analisis Strategi Peningkatan Kepuasan Pada Produk Xiomi - Iis Mariyam; Tasya Aulia; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Mobile phones are a technology that is developing rapidly from year to year. Many new brands are emerging in the world cellphone competition that competes with each other to create products their flagship. Several factors can influence the decision consumer purchases, namely: brand image, price and product quality. Image A brand is an association of all available information about a brand The products, services and companies of this brand are the abstract of this journal article which reveals the background that mobile phones are a technology that is developing rapidly with the emergence of many new competing brands. Several factors that influence consumer purchasing decisions include brand image, price and product quality.